EFEKTIVITAS PENGGUNAAN INSTAGRAM DALAM MENGUKUR DAN MENINGKATKAN BRAND AWARNESS: STUDI PLATZ CAR WASH - Andriyanti, Reza; Syukriah Mathory, Eljihad Akbari (Politeknik STIA LAN Makassar, 2025)
Social media is a platform used to interact, build, share, and convey information to the general public. Currently, social media not only functions as a communication tool, but is also used for business purposes, including in promoting products and services. Instagram provides an opportunity for business owners to introduce their business identity and build interactions with customers more effectively. One thing that can build a brand is brand awareness. The car wash business is one of the business sectors that shows significant growth, along with the increasing number of motorized vehicles in various regions in Indonesia. Therefore, the purpose of this study is to analyze and develop optimal strategies in managing Instagram social media to increase Platz Car Wash Consumer Brand Awareness. The research method used in this study is a qualitative approach with a descriptive research type by collecting data through observation, interviews and documentation. The data sources used in this study are primary and secondary data. The results of this study are in the form of video content to prove the effectiveness in promotion and brand awareness. videos produced with an attractive visual strategy.